BINDING OF ENDOTHELIN-1 TO HUMAN BLOOD MONOCYTE - Achmad, Tri Hanggono; S. Rao, Govind (Faculty of Medicine, Universitas Padjadjaran)
Monocyte attachment to the endothelium and migration into the vessel intima are the initiating steps in atherogenesis. This is thought to be facilitated by endothelin-1 (ET-1) as a potent chemoattractant to human blood monocytes. To explore the presence of ET-1 receptor(s) on the monocyte, we studied the binding of ET-1 to freshly isolated human blood monocytes, in the laboratory of the Institute of Clinical Biochemistry, University of Bon, Germany in 1995. Radioligand binding studies revealed the presence of two distinct subclasses of binding sites with apparent dissociation constants, K s, of 10.3 pM and 3.5 nM and maximal binding capacities, B s, of 0.027 fmol and 0.63 d max fmol/1.5x105 cells. Using monocyte migration as a response to ET-1, and ET-1 receptor antagonists BQ-123, BQ- 18257B and IRL-1038, the presence of two ET receptor subtypes, ET and ET , were detected. These results suggest A B that the chemotactic stimulus introduced by ET-1 can be activated ET-1 specific receptors on the monocytes.Key words: Endothelin-1, monocyte, receptor-bindingIKATAN ENDOTELIN-1 PADA MONOSIT DARAH MANUSIAMenempelnya monosit ke permukaan endotel dan bermigrasi kedalam tunika intima merupakan langkah awal pada aterogenesis. Hal ini diduga diperantarai oleh peran endotelin-1 (ET-1) yang dikenal sebagai chemoattractant poten bagi monosit. Untuk mengungkapkan adanya reseptor ET-1 pada monosit, dilakukan penelitian ikatan ET-1 pada monosit yang diisolasi dari darah manusia, di laboratorium Institute of Clinical Biochemistry, Universitas Bonn, Jerman pada tahun 1995. Penilaian ikatan radioligand menunjukkan adanya dua subkelas berbeda dari tempat ikatan dengan konstanta disosiasi (K ) masing-masing 10,3 pM dan 3,5 nM, serta kapasitas ikatan maksimal (B ) d max masing-masing sebesar 0,027 fmol dan 0,63 fmol/1,5x105 sel. Dari hasil penilaian tingkat migrasi monosit sebagai respons terhadap ET-1 dengan atau tanpa beberapa antagonis reseptor ET-1, BQ-123, BQ-18257B dan IRL-1038, terdeteksi adanya dua subtipe reseptor ET, yaitu ET dan ET . Hasil ini menunjukkan bahwa rangsangan kemotaksis A B yang ditimbulkan ET-1 dapat mengaktifkan reseptor spesifik ET-1 pada monosit.Kata kunci: Endotelin-1, monosit, ikatan-reseptor DOI: http://dx.doi.org/10.15395/mkb.v41n2.185